2021
DOI: 10.3390/electronics10111304
|View full text |Cite
|
Sign up to set email alerts
|

CogniViTra, a Digital Solution to Support Dual-Task Rehabilitation Training

Abstract: This article focuses on an eHealth application, CogniViTra, to support cognitive and physical training (i.e., dual-task training), which can be done at home with supervision of a health care provider. CogniViTra was designed and implemented to take advantage of an existing Platform of Services supporting a Cognitive Health Ecosystem and comprises several components, including the CogniViTra Box (i.e., the patient terminal equipment), the Virtual Coach to provide assistance, the Game Presentation for the rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Recent systematic reviews in aging and chronic diseases [ 22 , 26 - 28 ] have showed that CMDT interventions are beneficial for cognitive and motor function. The efficacy and engagement of CMDT rehabilitation could be improved by adopting interactive technological systems that enable one to monitor, aid, and empower cognitive-motor functions in aging [ 28 , 30 , 31 ]. In particular, VR equipped with motion sensors allows for the design of rehabilitative scenarios that involve the participants in cognitive and motor activity in a multisensory way and close-to-real-world conditions [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent systematic reviews in aging and chronic diseases [ 22 , 26 - 28 ] have showed that CMDT interventions are beneficial for cognitive and motor function. The efficacy and engagement of CMDT rehabilitation could be improved by adopting interactive technological systems that enable one to monitor, aid, and empower cognitive-motor functions in aging [ 28 , 30 , 31 ]. In particular, VR equipped with motion sensors allows for the design of rehabilitative scenarios that involve the participants in cognitive and motor activity in a multisensory way and close-to-real-world conditions [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews in aging and chronic diseases [22,[26][27][28] have showed that CMDT interventions are beneficial for cognitive and motor function. The efficacy and engagement of CMDT rehabilitation could be improved by adopting interactive technological systems that enable one to monitor, aid, and empower cognitive-motor functions in aging [28,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health Platform [20,21,22,23], which was implemented to minimize the critical sustainability issues for the cognitive health management by increasing the capacity to early identify and monitor all individuals at risk for cognitive decline and to provide early cognitive interventions with the adequate quality, intensity, and duration to obtain relevant functional effects. For this purpose, the Cognitive Health Platform promotes the use of innovative technological solutions to support different clinical domains: i) population-based cognitive screening strategies; ii) optimization of the neuropsychological rehabilitation processes by providing strategies to allow individual or group cognitive training programs, ideally at home or in community-based institutions; iii) rapid mobilization of the knowledge produced to improve the cognitive health of the populations in terms of intellectual performance, social participation, and quality of life.…”
Section: Platform Conceptmentioning
confidence: 99%